2010
DOI: 10.1002/mame.200900285
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Fluid Assisted Injection Molded Polycarbonate/Polyethylene Blends

Abstract: This study aims to examine the morphological development in fluid assisted injection molded high density polyethylene (HDPE)/polycarbonate (PC) blends. Samples for microscopic observation were prepared by an 80‐ton injection‐molding machine equipped with a tube cavity and with both gas and water injection units. It was observed that the shape and size of the dispersed phase depended on the position both across the part thickness and along the flow direction. Water molded parts with a smaller PC particle distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…The samples taken from the outer layer, middle layer, and inner layer showed a similar melting peak and crystallinity at position near the end of water channel. Liu et al found that material at the mold‐side exhibited a higher degree of crystallinity than that at the water‐side, and the crystallinity at the water‐side layer increased with increasing the water temperature, which was consistent with the reported results . In addition, for the WAIM–molded nylon 6 (PA6) parts, it was found that the γ‐phase crystals and α‐phase crystals, respectively, dominated the crystal morphology at the skin and intermediate layers, but the coexistence of the γ‐ and the α‐phase crystals dominated at the water‐channel layer…”
Section: Current Researchsupporting
confidence: 71%
See 3 more Smart Citations
“…The samples taken from the outer layer, middle layer, and inner layer showed a similar melting peak and crystallinity at position near the end of water channel. Liu et al found that material at the mold‐side exhibited a higher degree of crystallinity than that at the water‐side, and the crystallinity at the water‐side layer increased with increasing the water temperature, which was consistent with the reported results . In addition, for the WAIM–molded nylon 6 (PA6) parts, it was found that the γ‐phase crystals and α‐phase crystals, respectively, dominated the crystal morphology at the skin and intermediate layers, but the coexistence of the γ‐ and the α‐phase crystals dominated at the water‐channel layer…”
Section: Current Researchsupporting
confidence: 71%
“…Wang and Huang suggested that lowering the melt temperature is favorable for the formation of β‐form in the WAIM PP part ( Figure a,b). However, Lin and Liu reported that no β‐form was found in the WAIM part, but a larger amount in the CIM part. They explained that this phenomenon was attributed to fast solidifying rate brought by the injected water that left short time for the growth of the β‐phase on the formed α‐row nuclei.…”
Section: Current Researchmentioning
confidence: 98%
See 2 more Smart Citations
“…FAIM can enable greater freedom of design, material savings, weight reduction, and cost savings in tooling and press capacity requirements [4]. CIM can be used to produce parts with special characteristics by the combination of two or more types of plastic materials, such as using the outer material to achieve required surface properties, while using the core material to obtain sufficient mechanical properties or to reduce cost [7,8].…”
Section: Introductionmentioning
confidence: 99%